Historical aspects on special education in mathematics - Magne, Olof (NOMAD Nordic Studies in Mathematics Education, 2006)
Research on failure to master mathematics (often used term: disability) is a modest speciality, compared with related domains. Research on low attaining persons appears to be too much directed towards a small number of topics en vogue while other issues, often more impressive ones, are mainly left unnoticed. Not the least disquieting is the excessive concentration on computation with small natural numbers in a setting of formalism. This presentation has the aim to demonstrate that the number of parameters (factors, vectors, dimensions) is great in the field of research on education and learning mathematics and that research is a problematic matter, due to the complex relations between mathematics, individual and environment (MIE).